(untitled) (LIS TODAY, 2021)
Public Libraries play a significant role in the development of society. Library legislation broadly means legal permission for establishing a public library system and its maintenance, service, function, and management under any state or national authority. This paper discusses the importance of the public library in India and the role of an Indian library professional association. The evolution and status of the public library movement and the professional association of library and information science discipline in India has been reviewed critically. The study emphasizes on the requirement and successful implementation of library legislation for the development of Indian public libraries. The paper discusses the Indian states which have implemented public library legislation and the role of Indian library professional associations in the promotion and development of the public libraries in India. The purpose of Indian Library Professional Associations in helping these states to implement the library legislation has also been studied.